The term cotwin with spatial pulmonary lesions and elevated maternal-neonatal D-dimer levels following single intrauterine fetal death in a monochorionic-monoamniotic twin pregnancy: a case report and literature review - Haiyan Liu; Xiaoyue Zhang; Zhenzhen Liu; Yi Yu; Weirong Gu (BMC Pediatrics)
Abstract Background Complications such as cerebral impairment, preterm delivery, and even intrauterine death can occur in monochorionic twin pregnancies with singleton fetal death. The coagulation functions of the surviving fetus and mother remain controversial. Case presentation We reported a case of spontaneous single intrauterine fetal death at 17 weeks of gestation in a monochorionic monoamniotic twin pregnancy, followed by increased maternal and neonatal D-dimer levels and spatial pulmonary lesions in the surviving term cotwin, without cerebral impairment. The mother experienced significant postpartum pelvic hematoma, which was managed with conservative treatment and resolved. Conclusions Monitoring maternal and neonatal D-dimer, along with a detailed examination of the respiratory system and brain impairment of the surviving cotwin and newborn, maybe is crucial. This could be especially relevant in monochorionic monoamniotic twin pregnancies complicated by placental arterio-arterial or veno-venous anastomoses and elevated maternal D-dimer levels.